Research on Reliability of 3D Composite Phase Change Heat Dissipation Technology Applied in Rail Transit Vehicles - Yanping CHEN; Guomeng SONG; Zechun DOU; Nan HUANG; Xiao ZHANG; Biao XIANG (机车电传动)
In this paper, the reliability of 3D composite phase change heat dissipation technology for the rail transit vehicle converter was tested and verified based on the external environment and its self characteristics. The stability of the working medium was analyzed by GC-MS and ICE-MS firstly, and the heat dissipation performance of the heatsink was tested. The shock resistance and anti-vibration performance, heat and cold tolerance, corrosion resistance and pressure blast resistance of the heatsink were tested in harsh environments. The results showed that the 3D composite phase change heat dissipation technology has credible stability and reliability, which satisfies the conditions of vehicles running on plateau, alpine cold, coastal environment, and its frequent vibration conditions. More than 2 000 pieces of 3D composite phase change heatsinks has been installed on CRH380A after the 1.2 million kilometers on board functional assessment, and no failure has occurred in the past 3 years, so that the reliability of the 3D composite phase change technology was verified.